Low Civility and High Incivility in Russian Online Deliberation: A Case of Political Talk in Vkontakte Social Network - Daniil, Volkovskii; Olga, Filatova (KOME, 2023)
One of the most studied fields in deliberative research is (in)civility in Internet-based political discussions on issues of common concern. Uncivil behaviour demonstrated by participants in online communication has various forms and negative effects on the process and outcomes of e-deliberation as well as on deliberators’ reactions and attitudes, which have been predominantly investigated in Western democracies. However, this issue has been poorly covered in the countries with less stable democratic traditions and values. This paper explores speech culture with a focus on civility and incivility in Russian political conversations conducted on Russian social media. The authors analyse mass-scale web political discussions on a polarising issue of the court sentence of the politician Alexei Navalny (2021), taking one of the most popular Russian social networks VKontakte. For this study, scholars use discourse analysis based on the works on deliberative democracy proposed by J. Habermas (1996). They conclude that Russian political speech regarding Navalny’s sentence and conducted on the VKontakte social media platform can be characterised by a great extent of uncivil speech unbalanced by a low extent of civil speech. The conversations are not oriented towards mutual recognition or reaching a consensus, as participants are often distracted from the main issue being discussed, and turn to interpersonal topics instead.